Global, regional, and national burden of diabetes in women of childbearing age, 1990–2021: a systematic analysis from the global burden of disease study 2021 - Zhifeng Guo; Wangquan Ji; Mengqing Yan; Xianan Zou; Teng Chen; Fanghui Bai; Yu Wu; Zhe Guo; Linlin Song (Frontiers in Global Women's Health, 2025)
IntroductionDiabetes may have long-term adverse health effects on both women of childbearing age (WCBA) and their future generations. The objective of this study is to provide up-to-date epidemiologic information on the global burden of diabetes in WCBA to inform the development of targeted public health policies.MethodsThe data on the burden of diabetes among WCBA from 1990 to 2021 at the global, regional, and national levels were extracted from the Global Burden of Disease 2021 database. The estimated annual percentage change (EAPC) and Bayesian age–period–cohort models were used to assess and predict time burden trends. The slope index and concentration index were used to assess health inequalities associated with the sociodemographic index (SDI).ResultsIn 2021, approximately 79.04 million WCBA aged 15–49 years were living with diabetes, resulting in approximately 7.82 million disability-adjusted life years (DALYs). From 1990 to 2021, the age-standardized prevalence rate (ASPR) increased from 1960.8 to 3942.2 per 100,000 WCBA, with an EAPC of 2.25%. The ASPR and age-standardized DALY rate were highest in the low-middle SDI region, at 4,107.0 and 472.3 per 100,000, respectively. DALYs and deaths are concentrated in low SDI countries. By 2040, the global burden of diabetes in WCBA will increase further.ConclusionThe global burden of diabetes among WCBA has increased over the past three decades. This burden is concentrated in low- and middle-income countries. Diabetes care policies for WCBA urgently need to be improved and popularized.